870nm bragg grating in single mode topas microstructured polymer optical fibre - Kalli, Kyriacos; Yuan, Wu; Stefani, Alessio; Webb, David J.; Nielsen, Kristian; Rasmussen, Henrik Koblitz; Bang, Ole (My University, 2011)
We report the fabrication and characterization of a fiber Bragg grating (FBG) with 870 nm resonance wavelength in a single-mode TOPAS microstructured polymer optical fiber (mPOF). The grating has been UV-written with the phasemask technique using a 325 nm HeCd laser. The static tensile strain sensitivity has been measured as 0.64 pm/μstrain, and the temperature sensitivity was -60 pm/°C. This is the first 870nm FBG and the first demonstration of a negative temperature response for the TOPAS FBG, for which earlier results have indicated a positive temperature response. The relatively low material loss of the fiber at this wavelength compared to that at longer wavelengths will considerably enhance the potential utility of the TOPAS FBG.
Proceedings of SPIE - The International Society for Optical Engineering
Keywords: Lasers; Fibers; Optical fibers